Melamine and Cyanuric Acid in Milk and Their Quantities, Analytical Methods and Exposure Risk: A Systematic Review and Meta-analysis - Amirhossein Abedini; Zahra Hadian; Mahdie Kamalabadi; Mahla Salimi; Paliz Koohy-Kamaly; Burhan Basaran; Parisa Sadighara (Journal of Food Protection, 2025)
Melamine, as a toxic compound, needs to be controlled in food, especially in dairy products. In this systematic study, quantities of melamine and cyanuric acid in various types of milk were investigated. A comprehensive database search was performed using the keywords pasteurized milk, milk, sterilized milk, melamine, and cyanuric acid without time limitation. A total of 24 articles related to melamine and cyanuric acid were thoroughly reviewed. The overall mean concentration of melamine in milk was estimated by meta-analysis to be 11.3 μg/L. Publication bias was not addressed in the associated assays; however, it was addressed as highly heterogeneous between studies. Subgroup analysis was carried out, and the milk type was a cause of heterogeneity. This systematic review investigated a range of melamine in milk products and discussed different analytical methods.